2012
DOI: 10.1111/j.1365-3040.2012.02598.x
|View full text |Cite
|
Sign up to set email alerts
|

UVB radiation and 17‐hydroxygeranyllinalool diterpene glycosides provide durable resistance against mirid (Tupiocoris notatus) attack in field‐grown Nicotiana attenuata plants

Abstract: Depending on geographical location, plants are exposed to variable amounts of UVB radiation and herbivore attack. Because the role(s) of UVB in the priming and/or accumulation of plant defence metabolites against herbivores are not well understood, we used field-grown Nicotiana attenuata plants to explore the effects of UVB on herbivore performance. Consistent with previous reports, UVB-exposed plants accumulated higher levels of ultraviolet (UV)-absorbing compounds (rutin, chlorogenic acid, cryptochlorogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 89 publications
(185 reference statements)
1
67
0
Order By: Relevance
“…S5), the levels of CHA and DCS were rather similar or even lower in 48-h WOS-treated leaves compared with untreated controls. Differences in the accumulation patterns between CP and DCS (or CHA) were already noticed in several other independent studies (Kaur et al, 2010;Onkokesung et al, 2012;Dinh et al, 2013;Woldemariam et al, 2013). This suggests that simulated herbivory attack maintains, in a NaHER1-dependent manner, the higher levels of the "semiconstitutive" DCS (and possibly CHA) metabolites in the naturally aging leaves that can be considered as another part of the N. attenuata defense strategy.…”
Section: Fac Perception and Naher1 Are Required For The Contribution mentioning
confidence: 57%
See 1 more Smart Citation
“…S5), the levels of CHA and DCS were rather similar or even lower in 48-h WOS-treated leaves compared with untreated controls. Differences in the accumulation patterns between CP and DCS (or CHA) were already noticed in several other independent studies (Kaur et al, 2010;Onkokesung et al, 2012;Dinh et al, 2013;Woldemariam et al, 2013). This suggests that simulated herbivory attack maintains, in a NaHER1-dependent manner, the higher levels of the "semiconstitutive" DCS (and possibly CHA) metabolites in the naturally aging leaves that can be considered as another part of the N. attenuata defense strategy.…”
Section: Fac Perception and Naher1 Are Required For The Contribution mentioning
confidence: 57%
“…cDNA synthesis, real-time quantitative PCR (qPCR), and calculation of relative transcript abundances of genes of interest were performed as described (Pfaffl et al, 2002;Dinh et al, 2013). The primer sequences used for qPCR (SYBR Green assays) are listed in Supplemental Figure S16.…”
Section: Analysis Of Gene Expression By Real-time Quantitative Pcrmentioning
confidence: 99%
“…[36]. However, when single defense compounds were silenced, both DTGs [32, 37] and TPIs [38] emerged as clear determinants of T. notatus host choice.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found negative correlation between total leaf HGL-DTG content and the mass of the larvae that feed on them (Jassbi et al, 2008;Dinh et al, 2013). Eleven HGL-DTGs that differ in sugar moieties and number of malonylesters have been isolated from Nicotiana attenuata.…”
mentioning
confidence: 99%